Climate resilience through natural regeneration in degraded natural forests of south-eastern hilly region of Bangladesh - Bhuiyan, Md Khayrul Alam; Hossain, Md Akhter; Kamal, Abdul Kadir Ibne; Hossain, Mohammed Kamal; Jashimuddin, Mohammed; Uddin, Md Khabir (Bangladesh Journal of Botany, 2019)
A study was conducted by using 5m × 5m sized 179 quadrates following multistage random sampling method for comparative regenerating tree species, quantitative structure, diversity, similarity and climate resilience in the degraded natural forests and plantations of Cox's Bazar North and South Forest Divisions. A total of 70 regenerating tree species were recorded representing maximum (47 species) from degraded natural forests followed by 43 species from 0.5 year 39 species from 1.5 year and 29 species from 2.5 year old plantations. Quantitative structure relating to ecological dominance indicated dominance of Acacia auriculiformis, Grewia nervosa and Lithocarpus elegans seedlings in the plantations whereas seedlings of Aporosa wallichii, Suregada multiflora and Grewia nervosa in degraded natural forests. The degraded natural forests possess higher natural regeneration potential as showed by different diversity indices. The dominance-based cluster analysis showed 2 major cluster of species under one of which multiple sub-clusters of species exists. Poor plant diversity and presence of regenerating exotic species in the plantations indicated poor climate resilience of forest ecosystem in terms of natural regeneration.